Effect of the angle of apical resection on apical leakage, measured with a computerized fluid filtration device - GARİP, HASAN (MOSBY-ELSEVIER, 2011)
Objective. We determined the effect of the angle of apical resection on apical leakage using a computerized fluid filtration meter with a laser system and a digital air pressure regulator in 46 extracted single-rooted human teeth. Orthograde endodontic treatment was performed. The root canals were prepared up to a size 50 K-type file with 17% EDTA solution (Roth International, Chicago, IL) and 5% NaOCl solution as the irrigant. Gates Glidden burs (Maillefer Instruments, Ballaigues, Switzerland) were used to flare the coronal two thirds of the canal. All canals were dried with paper points and then obturated using cold lateral condensation (except for the positive controls) of gutta-percha points and AH plus (Dentsply DeTrey, Konstanz, Germany). All 40 roots were sectioned 3 mm from the apex. Forty teeth were assigned randomly into 1 of 4 experimental groups of 10 teeth each: in group 1, the teeth were resected apically (90 degrees angle) and the cavities were obturated with mineral trioxide aggregate (MTA); in group 2, after apical resection (90 degrees angle), a root-end cavity was prepared using ultrasonic diamond retrotips and the cavities were obturated with MTA; in group 3, the teeth were resected apically (similar to 45 degrees angle) and the cavities were obturated with MTA; and in group 4, after apical resection (similar to 45 degrees angle), a root-end cavity was prepared using ultrasonic diamond retrotips and the cavities were obturated with MTA. An additional 6 teeth were used as controls (3 each, negative and positive controls). Apical leakage was measured using a computerized fluid filtration meter with a laser system. Results. The mean apical microleakage was 2.0 +/- 0.4 x 10(-4), 1.6 +/- 0.6 x 10(-4), 1.6 +/- 0.9 x 10(-4), and 1.8 +/- 0.7 x 10(-4) mu L/cmH(2)O/min(-1) at 1.2 atm, in groups 1 to 4, respectively. Although the mean apical microleakage was greater in group 1, the differences among the 4 groups were not statistically significant (P > .05). Conclusions. The results of these in vitro studies showed that when an adequate retrograde cavity depth is prepared, variation in the root-end cutting angle does not necessarily cause any difference in microleakage. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2011;111:e50-e55)
Keywords: END FILLING MATERIALS; MINERAL TRIOXIDE AGGREGATE; ROOT-END; BACTERIAL LEAKAGE; ENDODONTIC TREATMENT; SEALING ABILITY; DYE LEAKAGE; MICROLEAKAGE; PENETRATION; PULP